1981
DOI: 10.1007/bf01721214
|View full text |Cite
|
Sign up to set email alerts
|

Pseudohypoparathyroidism and hypocalcemic “myopathy”

Abstract: A patient with the clinical features of pseudohypoparathyroidism and elevated concentrations of serum CK and LDH, which normalized after successful therapy, is described. Clinical signs of myopathy did not exist. The bioptical material from the m. tibialis anterior was microscopically normal. The biochemical analysis revealed a reduced phosphorylase-a-activity with the total phosphorylase-activity (a and b) being within the normal range. The significance of these findings as well as possible pathogenetic mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…If this is the case, then the CK increase would not be secondary to tetany alone, and hypocalcemic myopathy would represent a distinct pathological entity 4 . The histological findings in our case are in agreement with the literature descriptions of mild alterations and no structural or inflammatory lesions at biopsy, indicating a mild, non-specific myopathy which supports the hypothesis of a functional change in striated muscle 4,11,13,14 . The very low serum levels of PTH, hypocalcemia and hyperphosphatemia seen in the patient are the characteristic findings of IHP.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…If this is the case, then the CK increase would not be secondary to tetany alone, and hypocalcemic myopathy would represent a distinct pathological entity 4 . The histological findings in our case are in agreement with the literature descriptions of mild alterations and no structural or inflammatory lesions at biopsy, indicating a mild, non-specific myopathy which supports the hypothesis of a functional change in striated muscle 4,11,13,14 . The very low serum levels of PTH, hypocalcemia and hyperphosphatemia seen in the patient are the characteristic findings of IHP.…”
Section: Discussionsupporting
confidence: 92%
“…In this cases, however, CK tends do be normal 7 , whereas in our case it was strikingly elevated. Since the first description by Wolf et al , there have been very few cases of hypocalcemic myopathy with an increased CK, and almost all of them were due to IHP 1,2,[8][9][10] , but this finding can also be observed in pseudohypoparathyroidism 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this notion is based on observations of a single case, and this patient. In this regard, it is noteworthy that peripheral neuropathy and metabolic myopathy have been reported in patients with primary hypoparathyroidism [8,9], whereas such symptoms have not been described in patients with PHP, except for mildly elevated blood CK and lactate dehydrogenase (LDH) levels in a single case of PHP-Ia [10]. Moreover, in vitro experiments showed that calcium concentration affects excitability at neuromuscular junctions [11].…”
Section: Resultsmentioning
confidence: 99%
“…However, such clinical features have been rarely described in patients with PHP-Ib [10]. Here, we report a Japanese patient with familial PHP-Ib due to an intragenic deletion of STX16, who presented with unique neuromuscular symptoms.…”
Section: Molecular Analysesmentioning
confidence: 85%
“…Another unusual finding in our patient with hypocalcaemia was markedly increased level of serum muscle enzymes. This phenomenon has rarely been reported in patients with hypocalcaemia and myopathy due to hypoparathyroidism [5][6][7][8][9]. While myopathy in long lasting hypocalcaemia associated with osteomalaciais well described, it is not followed by an increase in serum CK levels [10].…”
Section: Discussionmentioning
confidence: 99%